Extrauterine Causes of Severe and Concealed Postpartum Bleeding: Clinical Aspects and Challenges - JM Palacios-Jaraquemada; AJ Nieto-Calvache; AN Basanta; Yang Pan; Jue Li (Maternal-Fetal Medicine)
Abstract. Objective. To describe the challenges in diagnosing concealed postpartum bleeding, a rare but potentially life-threatening condition, and to highlight key factors in identifying and managing this condition. Methods. We reviewed clinical cases and diagnostic approaches where concealed postpartum bleeding was suspected, focusing on the role of imaging, serologic markers, and angiography. We examined instances of hemodynamic instability, the utility of pelvic space analysis via computed tomography, and the limitations of digital angiography, particularly in identifying bleeding sources in the posterior iliac internal artery division. Results. Concealed postpartum bleeding often originates from venous damage or, less commonly, arterial injury. Hemodynamic instability was noted to occur periodically, despite negative findings on vaginal examination and ultrasound, leading to diagnostic delays. Digital angiography often yields negative results when the focus is limited to the anterior division of the internal iliac artery. Bleeding typically arises from damage to the vaginal muscular layer or levator ani muscle, both supplied by branches of the internal pudendal artery (posterior iliac division). In some cases, laparotomy also failed to locate the source due to the bleeding being in the subperitoneal spaces. Conclusion. Concealed postpartum bleeding presents a diagnostic challenge due to intermittent hemodynamic instability and often negative imaging results. A detailed pelvic space analysis and awareness of posterior iliac internal artery involvement are crucial. Advanced expertise, along with serologic markers of hidden bleeding, is essential for timely diagnosis and management.